The Impact of Triglyceride-Glucose Index Trajectories on Incidence and Recurrent Cardiovascular Events: Evidence from a Retrospective Cohort Study - Xu Y; Wu G; Jiang L; Yang X; Wen C; Yang Y; Hu H (Vascular Health and Risk Management, 2025)
Yuan Xu,1,* Gonglong Wu,2,* Long Jiang,3 Xinlei Yang,1 Chengjin Wen,4 Yulan Yang,5 Hui Hu6 1Medical Big Data Center, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 2School of Public Health, JiangxiMedical College, Nanchang University, Nanchang, People’s Republic of China; 3Department of Cardiology, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 4Quiclinic Technology Co., Ltd., Nanchang, People’s Republic of China; 5Department of Ophthalmology, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 6Department of Health Management Center, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hui Hu, Department of Health Management Center, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China, Email huhuiefy@163.comPatients and Methods: The study retrospectively collected 8086 clinical data from 2019 to 2021. Latent Class Trajectory Modeling (LCTM) was utilized to identify the longitudinal trajectories of the triglyceride-glucose index, and logistic regression was employed to analyze the relationship between different triglyceride-glucose trajectories and the incidence and recurrence of cardiovascular diseases.Results: During the study period, 1484 patients in the cohort experienced cardiovascular events. Using LCTM, three distinct triglyceride-glucose index trajectories were identified. In the overall cohort of recurrent patients, as well as among those with higher triglyceride-glucose levels (triglyceride-glucose > 8.309) within it, a high-gradual-increase trajectory was found to be significantly associated with cardiovascular disease risk compared to a low-stable trajectory. Similar observations were seen in incidence patients with higher triglyceride-glucose levels (OR 1.179; 95% CI 1.017– 1.368), which adjusted the demographic characteristics and the test indicators.Conclusion: A high baseline level of triglyceride-glucose index with a high-gradual-increasing trajectory was significantly associated with incidence and recurrence of cardiovascular disease. Early identification of such populations can aid in the prevention of both incidence and recurrent cardiovascular diseases in the future.Purpose: The triglyceride-glucose index is related to the cerebrovascular diseases. This study aimed to investigate the relationship between different triglyceride-glucose index trajectories and incidence and recurrence of cardiovascular disease.Keywords: cardiovascular diseases, triglyceride-glucose index, trajectory, incidence, recurrence